2021
DOI: 10.1289/ehp7932
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lead Levels in U.S. Children Ages 1–11 Years, 1976–2016

Abstract: Background: Lead can adversely affect child health across a wide range of exposure levels. We describe the distribution of blood lead levels (BLLs) in U.S. children ages 1–11 y by selected sociodemographic and housing characteristics over a 40-y period. Methods: Data from the National Health and Nutrition Examination Survey (NHANES) II (1976–1980), NHANES III (Phase 1: 1988–1991 and Phase II: 1991–1994), and Continuous NHANES (1999–2016) were used to describe the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(90 citation statements)
references
References 27 publications
5
84
1
Order By: Relevance
“…Even though lead-based house paint and leaded gasoline (for on-road vehicles) were banned in the US in 1978 [ 78 ] and 1996 [ 79 ], children remain at risk for ingesting lead via (1) drinking water provided through lead service lines (i.e., lead-containing plumbing) [ 80 ], (2) lead-contaminated dust and soil given the prior use of lead-based paint in older buildings [ 27 ], and (3) lead-contaminated topsoil from past leaded-gasoline vehicle emissions [ 81 ]. Indeed, while average blood lead levels have substantially declined over the past several decades, a 2021 study estimated that nearly 400,000 1-to-11-year-olds in 2011–2016 had blood-lead levels exceeding the CDC’s reference level of 5 μg/dL [ 82 ]. Here, about one in five houses in our participants’ neighborhoods were estimated to contain lead-based paint hazards, which is consistent with national surveys showing that 25% of United States housing stock contains one or more lead hazards [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though lead-based house paint and leaded gasoline (for on-road vehicles) were banned in the US in 1978 [ 78 ] and 1996 [ 79 ], children remain at risk for ingesting lead via (1) drinking water provided through lead service lines (i.e., lead-containing plumbing) [ 80 ], (2) lead-contaminated dust and soil given the prior use of lead-based paint in older buildings [ 27 ], and (3) lead-contaminated topsoil from past leaded-gasoline vehicle emissions [ 81 ]. Indeed, while average blood lead levels have substantially declined over the past several decades, a 2021 study estimated that nearly 400,000 1-to-11-year-olds in 2011–2016 had blood-lead levels exceeding the CDC’s reference level of 5 μg/dL [ 82 ]. Here, about one in five houses in our participants’ neighborhoods were estimated to contain lead-based paint hazards, which is consistent with national surveys showing that 25% of United States housing stock contains one or more lead hazards [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lead exposure commonly comes from old lead pipes, faucets, and plumbing fixtures. In addition to water contamination, nearly 23 million houses have lead-based paint hazards in the United States (Egan et al, 2021). Egan and his colleagues also found that there are more than 3.6 million households with children younger than six years old living in these lead-filled homes.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Lead exposure is one of the most common and well-known direct and indirect environmental diseases among children in the United States. The dust in older housing and leadbased paint is one of the primary sources of lead exposure among U.S children (Egan et al, 2021). Consumer products such as imported foods as well as lead exposure in the workplace are the other common sources of lead exposure (Ettinger et al, 2019).…”
Section: Agentmentioning
confidence: 99%
See 2 more Smart Citations